Digital Integration — Opportunities for German SMEs - Melanie Mesloh (Wirtschaftsdienst)
Abstract This article describes the level of digital integration of SMEs in Germany. For this purpose, it takes into account the share of selected digital technologies in the business activities of German SMEs. The article also explains advantages and barriers to digital integration and provides an evaluation of selected national framework conditions on the part of SMEs. Finally, the article highlights opportunities and challenges of digital integration in SMEs and presents possible areas for action.